มาตรการทางกฎหมายในการกำกับการทำธุรกรรมระหว่างบริษัทประกันภัยกับบุคคลที่เกี่ยวข้อง - นครินทร์ บุตรภักดีธรรม (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
This thesis has proposed to study the issues of the related party transaction of insurance company. The study covered related academic concept, theories and legal measures regulating related party transaction of Thailand and international legal measures. This study found that the transaction between insurance company and the related party who have influence in firm decision or have controlling power in firm could be the tunnel to extract the resources from firm to those influencers or controllers for their private benefit. This study also found that Thailand’s legal measures regulating transaction between insurance company and related party are insufficient due to the lack of legal measures covering all types of significant transaction, significant related party, standard of term and condition of the related party transaction, disclosure responsibility of insurance company regarding relationship with related party and related party transaction.Finally, this thesis proposes some amendments of the insurance laws of Thailand to be single standard in regards to related party transaction regulation of insurance company covering all significant types of transaction and related party, both quantitative and qualitative significance, by considering the influence in management decision or control in company. Furthermore, the law should provide standard of term and condition of related party transaction to meet at least arm’s length condition and provide reporting requirement from the insurance company to disclose the relationship with the related party and the related party transaction made by the insurance company to the supervisor directly for serving review in timely basis.